Development and validation of a DESI‐HRMS/MS method for the fast profiling of esomeprazole and its metabolites in rat plasma: a pharmacokinetic study. Issue 2 (28th April 2015) - Rossi, Alessandra; Castrati, Luca; Colombo, Paolo; Flammini, Lisa; Barocelli, Elisabetta; Bettini, Ruggero; Elviri, Lisa
Abstract : The advances in pharmaceutical development and drug discovery impose the availability of reliable high‐throughput screening methods for the rapid evaluation of drug metabolism and pharmacokinetic (PK) in biological samples. Here, a desorption electrospray mass spectrometry (DESI‐MS) method has been developed and validated for the PK profiling of esomeprazole and its metabolites (5‐hydroxyomeprazole and omeprazole sulfone) in rat plasma. Rats were treated with an esomeprazole solution (2.5 mg/mL) for endovenous administration and the analyte levels were profiled over 2 h after liquid‐liquid extraction from plasma. MS and tandem mass spectrometry (MS/MS) experiments were performed by using a DESI‐LTQ‐Orbitrap XL instrument and an on‐spot fixed time analysis on PMMA surfaces. Validation was performed for the esomeprazole. The DESI‐MS/MS method exhibited for the esomepazole excellent sensitivity (limit of detection (LOD)=60 ng/mL), linearity (0.2‐20 µg/mL concentration range; y=23848(±361)X, n=15; r 2 =0.987) and precision (RSD<9%) by using an internal standard method. The PK results were discussed in terms of Area Under the Curve, Cmax and Tmax . Data reliability was demonstrated by comparison with a liquid chromatography‐tandem mass spectrometry method (p>0.05). The data achieved demonstrated that the DESI‐MS method is suitable for sensitive and fast profiling of a drug and its metabolites at the therapeutic concentration levels. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A desorption electrospray mass spectrometry (DESI‐MS) method has been here developed and validated for the PK profiling of esomeprazole and its metabolites (5‐hydroxyomeprazole and omeprazole sulfone) in rat plasma. As for validation, the DESI‐MS/MS method showed for the esomeprazole excellent sensitivity (LOD = 60 ng/mL), linearity (0.2‐20 µg/mL concentration range; y = 23848(±361)X, n = 15; r 2  = 0.987) and precision (RSD<9%). The PK results were discussed in terms of Area under the Curve, Cmax and Tmax . Data reliability was demonstrated by comparison with a liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) method (p>0.05).